DETERMINAN KELELAHAN KERJA PADA PEKERJA SEBUAH HOTEL DI SANUR - Dewanthi, Putu Natasya; Wirawan, I Md Ady (ARCHIVE OF COMMUNITY HEALTH; Vol 11 No 3 (2024): Desember 2024, 2025)
Work fatigue is a complaint that is often experienced by workers due to the work they do. There are several factors that can increase the risk of burnout, both in terms of the individual and the job itself. This study aims to identify the factors that contribute to job burnout among hotel staff in Sanur. The research method used is quantitative research with an analytic approach and a cross-sectional design. Data was collected starting March 2023 from 54 hotel staff who were taken as a sample using the total sampling technique. Work fatigue was measured using the Industrial Fatigue Research Committee (IFRC) research scale, while physical workload was measured using the Physical Load Index (PLI) questionnaire. Data analysis was performed using univariate, bivariate, and multivariate analysis methods. The results of the analysis show that there is a relationship between several factors and work fatigue on the staff of a hotel in Sanur, on the work factor, namely the non-office field of work (aOR=4.81; 95% CI=1.14-20.36; p = 0.032) is the variable most related to the incidence of work fatigue. Instead, workers are placed in the field of work according to their abilities. Pay attention to the conditions of workers when working in their respective fields of work. Provide adequate rest hours for workers. Keywords: Work Fatigue, Individual Factors, Work Factors, IFRC, PLI